THE IMPACT OF AUTOMATION AND ROBOTICS ON MOTIVATION - Krecz, Péter; Herneczky, Andrea; Csernák, József; Baranyi, Aranka (Acta Carolus Robertus, 2021)
Special attention should be paid to the human factors that influence the competitiveness of companies when analysing the correlations of economic processes. It is no longer controversial today that human capital is an important and crucial factor in a company’s performance. The efficient, effective contribution of human resources to an organization’s success depends to a large extent on how it can ensure employees’ motivation in the long run. Robotics and automation are gaining more and more ground nowadays. In our study we explore how employee motivation is influenced by the rapid and widespread use of robotics. The industrial revolution that is still going on today is bringing enormous changes. The industrial revolutions that happened earlier in history have fundamentally changed the lives of people and have always posed serious challenges to various economic actors. Changes have had a dual impact in the past. On the one hand, industrial production has resulted in a change in the economy and, on the other hand, a huge change in the social structure. In recent years, mechanization has seemed extreme, but this phase must be seen today as a natural part of daily life.